Dampak Kebijakan Ekonomi dan Sosial Terhadap Pemahaman dan Praktik Iman dalam Masyarakat Pantura: Studi Kasus pada Masyarakat Pantura Kabupaten Indramayu - Sumarta; Romlah; Burhanudin (Khulasah : Islamic Studies Journal, 2020)
Abstract This research explores the intricate relationship between economic and social policies and the understanding and practices of faith in the Pantura community, focusing on the case of Indramayu Regency. The Pantura region of Indonesia is known for its rich cultural and religious diversity, making it an intriguing subject for examining how economic and social policies affect faith-related aspects of people's lives. The study employs a qualitative research design, utilizing interviews, surveys, and data analysis to uncover the multifaceted impact of policies on faith. The findings reveal a strong connection between socio-economic factors, such as income and education, and the depth of faith understanding and practice. Additionally, the local culture and traditions play a significant role in shaping the religious landscape, and policies promoting tolerance and interfaith dialogue are crucial in maintaining harmony in this diverse region. The research highlights the importance of holistic religious education, improved access to education and social services, and a nuanced understanding of how social and economic changes influence faith practices. Furthermore, it suggests the need for continued research to explore the evolving dynamics in this unique socio-religious context. Keywords: Economic Policies, Social Policies, Faith, Indramayu, Diversity.